Structural and phylogenetic insights from complete chloroplast genomes of seven Vicia species - Mohammad Mehdi Golchini; Aboozar Soorni (PLoS ONE, 2026)
The legume genus Vicia L. (Fabaceae) is of significant ecological and agronomic importance, comprising species widely utilized as forage crops, green manure, and sources of valuable phytochemicals. Despite this, a comprehensive genomic understanding of many species, particularly those endemic to underrepresented regions like Iran, remains limited. To address this, we employed a high-throughput sequencing and comparative genomics approach to elucidate the chloroplast (cp) genome architecture and evolutionary relationships of seven previously uncharacterized Iranian Vicia species including V. hirsuta , V. hybrida , V. lathyroides , V. lutea, V. narbonensis, V. peregrina , and V. villosa . Total genomic DNA was sequenced on an Illumina HiSeq 2000 platform, and the cp genomes were assembled de novo using GetOrganelle, followed by comprehensive annotation with a suite of bioinformatic tools. The analysis revealed considerable size variation, ranging from 118,660–130,223 bp, and a key structural divergence involving the loss of one inverted repeat (IR) region in six species, consolidating their placement within the IR-lacking clade (IRLC), while V. villosa retained the ancestral quadripartite structure. Lineage-specific gene losses were documented, including accD in V. lathyroides and ycf2 in V. narbonensis . Microsatellite analysis identified a predominance of A/T-rich mononucleotide simple sequence repeats (SSRs), with V. hybrida exhibiting the highest SSR density. Nucleotide diversity (Pi) analysis across coding regions identified clpP (Pi = 0.19772) and ycf1 (Pi = 0.16964) as hypervariable loci, while the ribosomal protein genes rps7 and rpl20 were validated as highly effective phylogenetic barcodes. Maximum likelihood phylogenetic reconstruction, based on a concatenated alignment of 86 shared protein-coding genes, resolved the species into well-supported clades, providing a robust evolutionary framework. This study delivers essential genomic resources that deepen the understanding of cp genome evolution in the IRLC and provides powerful molecular tools for future research in Vicia systematics, conservation genetics, and precision breeding.